Managing Aerospace Projects. - Williams, Jimmy (SAE International, 2017)
Over the next twenty years, the role and contributions of successfully managed projects will continue to grow in importance to aerospace organizations, especially considering the demands of emerging markets. The accompanying challenges will be how to effectively reduce product and process cost where known (incremental) and unknown (transformational) technological innovation is required. Managing Aerospace Projects brings together ten seminal SAE technical papers that support the vision of a more holistic and integrated approach to highly complex projects. Using the concept of project management.
Keywords: Aerospace industries.; Project management.; elektronické knihy; electronic books